Atividade lúdica no ensino de química : uma proposta de guia didático para o estudo de termoquímica - Martins, Genivania Silva Oliveira (2022)
This work falls within the scope of research dedicated to studies on the Teaching of Chemistry in Basic Education, in relation to the teaching and learning process in the content of Thermochemistry. With the general objective of providing didactic subsidies for the teaching of Thermochemistry to occur effectively, so that the concepts addressed within the theme are understood and built by students of Basic Education in a dynamic, meaningful and participatory way. Given the eminently abstract nature of Chemistry, recreational activities are configured as an important didactic strategy to promote the understanding of the more complex and abstract concepts present in the contents of Chemistry. Thus, to collaborate with Science Teaching, specifically Chemistry, in relation to Thermochemistry content, we investigated the pedagogical knowledge of chemical content of teachers of State Schools in the county of Campo Verde-MT, on the use of playful activities as a didactic strategy for the teaching of Thermochemistry. In this sense, the following guiding question is presented: how are the didactic strategies and activities of Chemistry teachers configured and expressed, when reporting the teaching on the concept of Thermochemistry that they carry out in Basic Education? To elucidate the proposed question, we resort to the conjectures of the qualitative method, based on the Case Study techniques, which deals with a bias focused on the study of a particularity, making it possible to systematize knowledge based on the experiences lived by the research participants, comprising how teachers develop their pedagogical practices. Data for analysis emerged from questionnaires and semi-structured interviews with participants. As a method of data analysis, Discursive Textual Analysis was used, as it allows a rigorous analysis and subsequent synthesis, enabling the construction of new knowledge, in order to expand the meanings of the researched phenomenon. It can be seen, from the bibliographic review and data analysis, in relation to the understanding of the concepts present in the content of Thermochemistry - such as heat, temperature, energy and processes of exothermic and endothermic reactions, among others - that much needs to be investigated, as they are concepts that bring a lot of confusion, regarding their understanding and this can corroborate with the lack of student interest in this theme. Thus, this research proposes an educational product in the form of a Didactic Guide, entitled Between everyday life and science: Thermochemical Debates, bringing playful activities on the concepts of Thermochemistry, such as Comics, for example, as a way of to collaborate with the teaching of these concepts in Basic Education, with the purpose of making the Chemistry class more dynamic and interactive, enabling, in broader terms, that students can become participatory and autonomous subjects of their own learning.